Strategic approach to configurational analysis of entrepreneurial orientation, strategic networking, and sme performance within emerging markets of selected Southeast European countries - Bojan Morić Milovanović; Mirjana Grčić Fabić; Vjekoslav Bratić (Administrative Sciences, 2023)
The beneficial relationship of entrepreneurial orientation with performance has been extensively acknowledged in the literature. However, empirical evidence is not straightforward and requires consideration of the interplay of different variables, context, and rationales through which this causal complexity of the performance-enhancing mechanism of entrepreneurial orientation influences firm performance. In this paper we examine the way the entrepreneurial behavior of the organization unfolds and affects performance through specific configurations resulting from the simultaneous interaction of strategic networking and dynamic environment in the setting of Southeast European SMEs. We apply hierarchical regression to a sample of 963 small and medium-sized enterprises. Empirical findings provide support for applying the configurational approach and show that companies of high entrepreneurial orientation and high strategic networking operating in a dynamic environment achieve the highest effect on a business performance. Research results further indicate that strategic networking is a mechanism that achieves the greatest efficiency in a dynamic environment and with the presence of a firm's entrepreneurial orientation. According to the research results, implications for research and practice are suggested.
Keywords: 350; configurational approach; entrepreneurial orientation; SMEs; Southeast Europe; strategic networking